2021
DOI: 10.3390/geomatics1040025
|View full text |Cite
|
Sign up to set email alerts
|

Validating Hourly Satellite Based and Reanalysis Based Global Horizontal Irradiance Datasets over South Africa

Abstract: This study validates the hourly satellite based and reanalysis based global horizontal irradiance (GHI) for sites in South Africa. Hourly GHI satellite based namely: SOLCAST, Copernicus Atmosphere Monitoring Service (CAMS), and Satellite Application Facility on Climate Monitoring (CMSAF SARAH) and two reanalysis based, namely, fifth generation European Center for Medium-Range Weather Forecasts atmospheric reanalysis (ERA5) and Modern-Era Retrospective Analysis for Research and Applications (MERRA2) were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…(2023a) reported that the MAE varies from 153 to 232 W m −2 for the rsds under cloudy skies for the reanalysis (ERA5 and MERRA‐2) and satellite (CAMS and SARAH‐2) products, compared to 37 observing stations over western Africa. Evaluation of satellite‐estimated rsds over South Africa (Mabasa et al., 2022) showed excellent performance under clear skies with rMAE smaller than 6.5% and poorer performance under cloudy skies with rMAE 29%, whereas satellite‐based rsds estimate outperform the reanalysis‐based estimate over South Africa (Mabasa et al., 2021). In addition, a dynamical downscaling study (Sawadogo et al., 2023b) using the WRF‐solar model driven by ERA5 also documented large overestimations for rsds under cloudy skies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2023a) reported that the MAE varies from 153 to 232 W m −2 for the rsds under cloudy skies for the reanalysis (ERA5 and MERRA‐2) and satellite (CAMS and SARAH‐2) products, compared to 37 observing stations over western Africa. Evaluation of satellite‐estimated rsds over South Africa (Mabasa et al., 2022) showed excellent performance under clear skies with rMAE smaller than 6.5% and poorer performance under cloudy skies with rMAE 29%, whereas satellite‐based rsds estimate outperform the reanalysis‐based estimate over South Africa (Mabasa et al., 2021). In addition, a dynamical downscaling study (Sawadogo et al., 2023b) using the WRF‐solar model driven by ERA5 also documented large overestimations for rsds under cloudy skies.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, both data sources have a larger error of more than 150 W m 2 (root mean squared error) under cloudy skies than under clear skies. Mabasa et al (2021) conducted an evaluation of GHI using two reanalyzes (ERA5 and MERRA2) and three satellite-based data sets (SOLCAST, CAMS, and SARAH-2) against 13 radiometric observations in South Africa. The study found that both types of data sets overestimate GHI, with less discrepancy observed in satellite-based GHI compared to reanalysis-based GHI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The models considered ranged from simple clear sky models (Berger-Duffie, ABCG, and Haurwitz) that require few input parameters (such as the sun's zenith angle (θ z ) and the top of the atmosphere's direct normal irradiance (DN I TOA )) to complex clear sky models (Ineichen and Perez, Bird, Simplified Solis) that require many input parameters in addition to θ z and DN I TOA , as summarized in Table 3. The SOLCAST satellite-based dataset was also included in the study because it performed best when validated against GHI observation data such as Mabasa et al [39] in South Africa, Yang and Bright [40] globally using Baseline Surface Radiation Network (BSRN) [41] stations, and Bright [42] in all climatic regions. It was included in the study to investigate the possibility of using it with ERA5 hourly fractional cloud cover data [43] in estimating clear sky irradiance.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of studies were conducted on ground-based data and satellite-based data [24][25][26][27][28][29]. Some of studies done in the past showed that there were various errors associated with satellite-based models and that is why there was a difference between solar data obtained from satellite models and ground measurements [30][31][32].…”
Section: Introductionmentioning
confidence: 99%